Fractional Differential Equations with Fractional Impulsive and Nonseparated Boundary Conditions - Xi Fu; Xiaoyou Liu (Abstract and Applied Analysis)
This paper studies the existence results for nonseparated boundary value problems of fractional differential equations with fractional impulsive conditions. By means of Schaefer fixed point theorem, Banach fixed point theorem, and nonlinear alternative of Leray-Schauder type, some existence results are obtained. Examples are given to illustrate the results.